Analisis Tematik Faktor-Faktor yang Mempengaruhi Keberhasilan Siswa dalam Pembelajaran Sains - Tae, Lidwina Felisima; Ramdani, Zulmi; Shidiq, Galih Albarra (Indonesian Journal of Educational Assessment, 2019)
Successful learning is determined by various factors involved in it. These factors are not only derived from the personal individuals involved themselves, but also are the result of collaboration between human resources and other resources in the same context. This study tries to explore the factors that determine a person's success in science learning. The study is conducted by identifying the attributes that are considered important in the learning process. Those involved in this study numbered 65 respondents who acted as teachers, educators, tutors, or lecturers who taught and focused on science materials. The method used is a thematic analysis approach that specifically categorizes the themes that are considered important and becomes the initial indicator in determining the success of learning. The results of the study show that a success in the learning process of science depends on the aspects in it including good collaboration between students and teachers, self-management, methods used in learning, applied evaluation strategies, as well as external factors which are not directly determines the success of learning such as the cultural, social, and environmental context in which the individual grows and develops.